2011
DOI: 10.1021/ja200838c
|View full text |Cite
|
Sign up to set email alerts
|

Boron Carbon Nitride Nanostructures from Salt Melts: Tunable Water-Soluble Phosphors

Abstract: A simple, high yield, chemical process is developed to fabricate layered h-BN nanosheets and BCNO nanoparticles with a diameter of ca. 5 nm at 700 °C. The use of the eutectic LiCl/KCl salt melt medium enhances the kinetics of the reaction between sodium borohydride and urea or guanidine as well as the dispersion of the nanoparticles in water. The carbon content can be tuned from 0 to 50 mol % by adjusting the reactant ratio, thus providing precise control of the light emission of the particles in the range 440… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
285
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 446 publications
(313 citation statements)
references
References 38 publications
27
285
1
Order By: Relevance
“…The spectra of both CNn and low-defected CNa show the typical IR patterns of graphitic carbon nitride (Fig.1b) [37]. The strong bands at 1200-1600 cm -1 are assigned to the stretching vibration of either trigonal C-N(-C)-C or bridging C-NH-C units in the heptazine heterocyclic ring (C6N7) units, while the sharp peak at ~810 cm -1 is considered as their breathing mode.…”
Section: Resultsmentioning
confidence: 98%
“…The spectra of both CNn and low-defected CNa show the typical IR patterns of graphitic carbon nitride (Fig.1b) [37]. The strong bands at 1200-1600 cm -1 are assigned to the stretching vibration of either trigonal C-N(-C)-C or bridging C-NH-C units in the heptazine heterocyclic ring (C6N7) units, while the sharp peak at ~810 cm -1 is considered as their breathing mode.…”
Section: Resultsmentioning
confidence: 98%
“…S1 is the Fourier transf orm infrared (FTIR) spectrum of the sample, showing two strong peaks at 1400 and 790 cm −1 that are assigned to characteristic absorption bands of B-N bond [35]. The vibrations of the C-related group were all overlapped by that of B-N.…”
Section: Resultsmentioning
confidence: 99%
“…Especially, theoretical and experimental investigations have indicated that visible light absorption and emission with tuneable wavelength can be achieved by controlling the carbon content in (B, N) rich BCN nanostructures, which then can be considered as metal-free light energy converters [33][34][35]. However, the study on this family of ternary photocatalysts is rather rare, although such materials fulfil basic requirements of photocatalysts, including being stable, visible-light responsive, and inexpensive.…”
Section: Science China Materialsmentioning
confidence: 99%
“…30,31 The incorporation of oxygen to the BCN system has drastically enhanced its color tuning range, which extends from violet to red regions of photoluminescence spectra. The theoretical calculations 21,30 and experimental evidence 19,[31][32][33][34][35][36] have indicated that tunable visible emissions with high quantum yields can be achieved using BCNO compounds which have metal-free phosphors with low toxicity properties. In addition, high external quantum efficiency and a broad range of excitation wavelengths also were obtained.…”
Section: Introductionmentioning
confidence: 99%